Innovation Strategy for Village Owned Enterprises (BUMDes) in Increasing Potential and Economic Welfare of Village Communities (Study on BUMDes Maccini Baji Bonto Jai Village, Bissapu District, Bantaeng Regency) - Saputra, Ikhwan; Madris; Nurbayani, Sri Undai (Economics and Business Journal (ECBIS), 2023)
Badan Usaha Milik Desa is agency business that was established by the Government of the village with capital beginning sourced from APB December to utilize all the potential economic, institutional economy as well as the potential source of the power of nature and the source of the power of man in order to improve the welfare of the community village. Research This aims to determine the role of BUMDes in utilizing the potential of the economy locally with a variety of potential which is owned by the village in order to improve the welfare of the economy of society villagers and encourage an increase in revenues native village. This research is a field, data collection techniques used in this study is a triangulation technique (observation, interview and documentation). The method of research is using the method of research qualitative descriptive. The results of this study are the role of BUMDes Sumber Sejahtera in increasing the potential and economic prosperity of the community in Pujonkidul Village through its programs and business units that can open new jobs for residents, increase community incomes and encourage increased PAD Desa.